A case report of late‐onset atypical Hemolytic Uremic Syndrome during interferon beta in multiple sclerosis: Open issues in literature review. Issue 1 (16th December 2020) - Parisi, Mosè; Manni, Alessia; Caputo, Francesca; Trojano, Maria; Paolicelli, Damiano
Abstract: Background and aims: Interferon beta (IFNβ) is a well‐established first‐line therapy for relapsing–remitting multiple sclerosis (RRMS) patients and remains the most widely prescribed agent. Atypical hemolytic uremic syndrome (aHUS) represents a rare but severe adverse effect (AE) that could occur even after many years from the beginning of IFNβ therapy. Eculizumab is currently approved for treatment of aHUS and recently for neuromyelitis optica spectrum disorder (NMOSD) with aquaporin‐4 antibodies (AQP4‐IgG). In this article, we report the case of the latest onset of IFNβ‐related aHUS experienced by an MS patient and we briefly review the literature on this topic. Methods: We performed a systematic review of the literature using PubMed, and we performed a retrospective analysis of RRMS patients that received IFNβ‐1a in our center and developed thrombotic microangiopathy (TMA). From this search, we identified only one patient. Results: In the published literature, we identified 24 MS patients who received IFNβ as disease‐modifying treatment (DMT) and then developed thrombotic microangiopathy with kidney injury. The aHUS has been diagnosed in 6, all received IFNβ‐1a and the latest onset was after 15 years. We report a case of a 39‐year‐old man affected by RRMS who assumed IFNβ‐1a since 1999. In July 2018, he developed an IFNβ‐related aHUS. After the failure of plasma exchange, he underwent eculizumab, with an improvement of glomerular filtration rate and without new signs of MS activity. Conclusion: To our knowledge, this case represents the latest onset of IFNβ‐related aHUS in MS patients. Up to now, there are not literary reports about the possibility to reintroduce a DMT as add‐on therapy to eculizumab. Abstract : Interferon‐beta (IFNβ) is a first‐line therapy for Relapsing‐Remitting Multiple Sclerosis (RRMS). Atypical Haemolytic Uremic Syndrome (aHUS) represents a rare but severe adverse effect (AE) that could occur even after many years from the beginning of IFNβ therapy. We report the case of the latest onset of IFNβ‐related aHUS experienced by an MS patient.